History of indigenous policies as trace of erythrocyte antigen dia in the current population of the american continent - Azzaro, Sebastián (2018)
Objective: The study aim to establish a debate on the different policies implemented at indigenous population in the American continent and their relationship with the presence of DiegoA antigen (AgDia) in blood phenotype of inhabitants of Buenos Aires,Argentina. Methods: It is a descriptive study with qualitative/quantitative approach. A comprehensive search of medical/social databases, using MeSH words. Limits were applied to include studies published after 1950 written in Portuguese, English and Spanish. Results: Dia antigen in the population of several American countries is relatively high, hence, it should be considered in screening panels perform to blood donors. Noteworthy, the exception of this panorama is Buenos Aires State, where the prevalence of this antigen is low. This data was correlated with indigenous policies carried out by former governments. The results showed in population living in regions where Dia is high policy performed by the colonizers towards the indigenous peoples was domination+integration+miscegenation. In Buenos Aires, however, that policy was annihilation of the natives which could explain the low presence of the antigen in the current population. Conclusion: The presence of Ag-Dia in the population of Buenos Aires is low compared to other Latin- American regions. The presence of Ag-Dia in Buenos Aires population is low compared to other regions of Latin-America. The reason could be explained by the distinctive indigenous policy performed in this area. It might be possible then to predict the prevalence Dia in the current population, taking into account the history of indigenous policy in colonization of American continent.